The effects of different types of Tai Chi exercises on motor function in patients with Parkinson's disease: A network meta-analysis - Lei, Honghui; Ma, Zhen; Tian, Kexin; Liu, Ke; Wang, Jiaying; Zhu, Xiangyu; Mi, Baohong; Chen, Ying; Yang, Qihao; Jiang, Huili (Frontiers in Aging Neuroscience, 2022)
Background: Tai Chi can make improvement in balance and motor ability of elderly PD patients. However, There were few reports of differences in outcomes associated with different types of Tai Chi on improving exercise capacity in elderly PD patients. We compared the improvement of motor function in Parkinson's patients with different types of Tai Chi, for finding an optimal intervention. Methods: The following databases were searched from the beginning of the establishment of each database to January 10 2022: PubMed, EMBASE, The Cochrane Library, CNKI, Wanfang Database, and VIP Database. Randomized controlled trials incorporating different types of Tai Chi for PD were included. The outcome measures were UPDRSIII and BBS. NMA was conducted by Stata 15.0 based on a frequentist framework. Results: Twenty trials were eligible, including 996 participants. In conventional meta-analysis, as for the UPDRSⅢ scale, the 24-form Tai Chi (SMD=-1.54, 95% CI [-2.20, -0.88], P < 0.05, I2 > 50%), Tai Chi exercise program (SMD=-0.72, 95% CI [-1.49, 0.05], P > 0.05, I2 > 50%), Yang style Tai Chi (SMD=-0.49, 95% CI [-1.30, 0.33], P > 0.05, I2 > 50%), and Chen style Tai Chi (SMD=-0.28, 95% CI [-0.97, 0.42], P > 0.05, I2 > 50%), were statistically more efficient than control group. For BBS outcome, 24-form Tai Chi (MD=3.98, 95% CI [3.36, 4.61], P < 0.05, I2 < 50%), Tai Chi exercise program (MD=5.00, 95% CI [2.07, 7.93], P > 0.05, I2 > 50%), Yang style Tai Chi (MD=3.83, 95% CI [-0.11, 7.77], P > 0.05, I2 > 50%), and Chen style Tai Chi (MD=1.25, 95% CI [0.52, 1.98], P < 0.05, I2 > 50%) were better than control group. In the network meta-analysis, the results of UPDRSⅢ were as follows: 24-form > TCEP > YS > CS > control. The ranking probability of BBS was: TCEP > YS > 24-form > CS > control. Conclusion: Among the four treatments studied, 24-form Tai Chi and Tai Chi exercise program have shown better efficacy than other types. Our study provides new insights into exercise therapy for PD and may contribute to the formulation of clinical exercise prescription.